2006
DOI: 10.1038/sj.leu.2404346
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival and low incidence of late toxic sequelae in advanced follicular lymphoma treated with a TBI-free autografting program: updated results of the multicenter consecutive GITMO trial

Abstract: This study provides an updated report of the consecutive multicenter Gruppo Italiano Trapianto Midollo Osseo trial employing an intensified, purging-free, total body irradiationfree, high-dose sequential chemotherapy schedule with peripheral blood stem cell autograft (i-HDS) in advanced-stage follicular lymphoma (FL). Special interest has been devoted to late toxicities and outcome in terms of molecular status. Ninetytwo untreated FL patients aged p60 were enrolled by 20 Italian centers and evaluated on an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Most studies showed that MRD negativity is associated with a superior outcome and acts as an independent predictor. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, a few studies failed to confirm this observation. [25][26][27][28] In particular, a recent report by van Oers et al 28 failed to demonstrate any benefit of achieving postinduction PCRnegative status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies showed that MRD negativity is associated with a superior outcome and acts as an independent predictor. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, a few studies failed to confirm this observation. [25][26][27][28] In particular, a recent report by van Oers et al 28 failed to demonstrate any benefit of achieving postinduction PCRnegative status.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The risk for recurrence is more pronounced among patients older than 60 years, as they often receive less-intense treatments. 4 Considerable evidence indicates that the persistence of polymerase chain reaction (PCR)-detectable residual tumor cells in the bone marrow (BM) and, to a lesser extent, peripheral blood is an independent predictor of relapse in FL [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ; nevertheless, a few studies have failed to confirm this observation. [25][26][27][28] Concerns about the value of minimal residual disease (MRD) detection as an effective prognostic tool have been raised, particularly when applied to The results of this study were the subject of an oral presentation at the 2012 American Society of Hematology annual meeting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prerituximab data suggest that HDS regimens might be associated with fewer second tumors compared with alternative autografting programs potentially because there is no TBI and large stem cell grafts are infused. 16,17 The present multicenter, open-label, randomized phase 3 trial took advantage of these observations. We compared a rituximab-supplemented version of HDS (R-HDS) with 6 courses of CHOP (cyclophosphamide/doxorubicin/vincristine/prednisone) supplemented by an identical number of rituximab courses (CHOP-R) in high-risk patients with FL.…”
mentioning
confidence: 99%
“…large series of studies [Gribben et al 1991a[Gribben et al , 1991b[Gribben et al , 1992Hardingham et al 1995;Corradini et al 1997;Moos et al 1998;Freedman et al 1999;López-Guillermo et al 1998;Apostolidis et al 2000;Rambaldi et al 2002Rambaldi et al , 2005Ladetto et al 2002Ladetto et al , 2006Ladetto et al , 2008Corradini et al 2004;Ghielmini et al 2004;Brown et al 2007;Hirt et al 2008;Goff et al 2009;Morschhauser et al 2012]. MRD can be detected using different methods, including cytogenetics, flow cytometry, PCR-based tools and potentially also with hightrough output sequencing methods [Faham et al 2012;Ladetto et al 2012a].…”
Section: Clinical Implications and Prognostic Role Of Minimal Residuamentioning
confidence: 99%